Nutritional quality and in vitro digestibility of fermented rice bran based on different types and doses of inoculants - Dilaga, Syamsul Hidayat; Putra, Ryan Aryadin; Pratama, Anggriawan Naidilah Tetra; Yanuarianto, Oscar; Amin, Muhamad; Suhubdy, Suhubdy (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The study was conducted to determine the effect of inoculants of different types and doses on the nutrient quality and in vitro digestibility of fermented rice bran. Materials and Methods: The study was designed using a completely randomized design with a 3 × 3-factorial pattern. The first factor was the type of inoculum, consisting of Saccharomyces cerevisiae (SC), Effective Microorganism-4, and Saus Burger Pakan (SBP). The second factor is inoculum doses, which are as follows: levels 2%, 4%, and 6%. The variables measured included chemical composition, fiber fraction content, dry matter digestibility and organic matter digestibility. Results: The results showed that the type of inoculation treatment and the doses of inoculation did not affect the dry matter (DM) content of fermented bran, and the organic matter content of fermented bran was only affected by the inoculation dose factor (p < 0.05). The highest crude protein and Extract Ether (EE) were obtained in the SBP inoculants, which increased linearly with increasing inoculation doses (p < 0.05). While a significant decrease (p < 0.05) occurred in crude fiber content. The cellulose, hemicellulose, lignin, acid detergent fiber (ADF), and neutral detergent fiber (NDF) fractions were significantly lower in the SBP treatment as the dose increased. The SBP inoculant type produced the highest DMD (p < 0.05) but showed a response that was not different from the SC inoculant treatment for OMD. Increasing inoculation doses of 2%, 4%, and 6% linearly increased the DMD and OMD of fermented bran (p < 0.05). Overall, inoculant application on fermented bran showed an interaction effect except for the components of DM, EE, ADF, NDF, and DMD of fermented bran. Conclusions: It was concluded that the SBP at 6% and their combination resulted in the best chemical quality and digestibility of rice bran. J. Adv. Vet. Anim. Res., 9(4): 625–633, December 2022 http://doi.org/10.5455/javar.2022.i632